“Something Better Left Alone”: Interrogating the Mother in Dolores Claiborne - Jay, Betty (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Based upon Stephen King’s 1992 novel, Taylor Hackford’s Dolores Claiborne (1995) takes a mother-daughter relationship as its dramatic focus. Estranged for fifteen years, Dolores St. George (Kathy Bates) and her daughter Selena (Jennifer Jason Leigh), are reunited when the former is accused of murdering her wealthy and aged employer. This meeting is anonymously facilitated by John Mackey (Christopher Plummer), a detective long-convinced of Dolores’ murderous propensities. Driven by his failure to prosecute her for the death of her husband, Joe, some eighteen years earlier, Mackey hopes Selena’s return will become the source of Dolores’ undoing. Equally convinced of her mother’s guilt for the earlier crime, Selena dutifully returns to their island-home where she calls upon her experience as a successful New York journalist to orchestrate Dolores’ defence. During her stay, she is forced by her mother to confront the events that led, during an historic solar eclipse, to Joe’s death. Although she initially rejects both her mother and the testimony she provides, Selena comes, at the close of the film, to face her own repressions and, in so doing, effects a reconciliation with the woman whose claims she has hitherto denied.